Incidence of extrapancreatic malignancies in patients with intraductal papillary mucinous neoplasms of the pancreas. Issue 9 (12th March 2011) - Kawakubo, Kazumichi; Tada, Minoru; Isayama, Hiroyuki; Sasahira, Naoki; Nakai, Yousuke; Yamamoto, Keisuke; Kogure, Hirofumi; Sasaki, Takashi; Hirano, Kenji; Ijichi, Hideaki; Tateishi, Keisuke; Yoshida, Haruhiko; et al.
Abstract : Background and aims: Intraductal papillary mucinous neoplasms (IPMNs) of the pancreas have been reported to be associated with extrapancreatic malignancies, but there have been no prospective studies evaluating the incidence of extrapancreatic cancers in patients with IPMNs. In this study, the frequency of patients with IPMNs developing extrapancreatic cancers during follow-up was examined. Methods: 642 patients with IPMNs were prospectively followed up for 4.8 years on average. They underwent clinical examination at least twice a year. The incidence of the observed extrapancreatic malignancies was compared with the expected incidence of the age- and gender-matched general Japanese population based on the Vital Statistics of Japan. Results: 40 extrapancreatic cancers developed in 39 patients during follow-up (1.3% per year). The most common malignancies were hepatocellular (n=7), colorectal (n=6), gastric (n=6), lung (n=5) and prostate cancers (n=4). The calculated standardised incidence rate of each of the malignancies was not significant, as follows: hepatocellular 2.17 (95% CI 0.87 to 4.47), colorectal 1.02 (0.37 to 2.21), gastric 0.76 (0.28 to 1.66), lung 0.75 (0.24 to 1.76) and prostate 1.00 (0.71 to 1.29). Pancreatic cancer was observed in 17 patients during the same period, with a standardised incidence rate of 10.7 (6.2 to 17.1). Conclusions: The incidence of extrapancreatic malignancies in patients with IPMNs was similar to that in the general population, whereas the incidence of pancreatic cancers was significantly high. Intraductal papillary mucinous neoplasms are not associated with systemic carcinogenesis except for pancreatic cancer.